2015
DOI: 10.1016/j.cej.2014.11.087
|View full text |Cite
|
Sign up to set email alerts
|

A concise review on microwave-assisted polycondensation reactions and curing of polycondensation polymers with focus on the effect of process conditions

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractDuring the past 15 years, increasing application of microwave heating to polycondensation reactions has been witnessed. Experiments have been carried out at laboratory scale using widely different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…The synthesis of polyesters and polyamides is carried out via the polycondensation reaction . As castor oil naturally contains ricinoleic acid, which can be obtained through hydrolysis, polycondensation can occur between the carboxyl group and hydroxy groups present in the fatty acid to produce polyesters.…”
Section: Castor Oilmentioning
confidence: 99%
“…The synthesis of polyesters and polyamides is carried out via the polycondensation reaction . As castor oil naturally contains ricinoleic acid, which can be obtained through hydrolysis, polycondensation can occur between the carboxyl group and hydroxy groups present in the fatty acid to produce polyesters.…”
Section: Castor Oilmentioning
confidence: 99%
“…Phase-transfer catalysis (PTC) is a performance that was conducting a reaction between reactant species existing in homogeneous or heterogeneous method [5] . Application of ultrasound or microwave irradiations are more common in PTC reactions rather than the conventional temperatures [6,7] . The major advantages of the PTC technique for preparing ethers are higher reaction rate, just needed low energy, selectivity and hydrophilic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave is a nonionizing electromagnetic energy and is widely used in the chemical eld recently. [11][12][13][14][15] Compared to the conventional heating method, microwave heating can reduce the activation energy of chemical reactions and induce orientation effects of dipolar molecules. [16][17][18] Imai et al investigated the microwave-assisted synthesis of polyamides and PIs and indicated that microwave is a facile and rapid method in the presence of appropriate solvents.…”
Section: Introductionmentioning
confidence: 99%